Enhancing Efficiency of Anaerobic Digestion by Optimization of Mixing Regimes Using Helical Ribbon Impeller - Buta Singh; Kornél L. Kovács; Zoltán Bagi; József Nyári; Gábor L. Szepesi; Máté Petrik; Zoltán Siménfalvi; Zoltán Szamosi (Fermentation, 2021)
The appropriate mixing system and approach to effective management can provide favorable conditions for the highly sensitive microbial community, which can ensure process stability and efficiency in an anaerobic digester. In this study, the effect of mixing intensity on biogas production in a lab-scale anaerobic digester has been investigated experimentally and via modeling. Considering high mixing efficiency and unique feature of producing axial flow, helical ribbon (HR) impeller is used for mixing the slurry in this experiment under various conditions. Three parallel digesters were analyzed under identical operating conditions for comparative study and high accuracy. Effects of different mixing speeds (10, 30, and 67 rpm for 5 min h−1) on biogas production rate were determined in 5-L lab-scale digesters. The results demonstrated 15–18% higher biogas production at higher mixing speed (67 rpm) as compared to 10 rpm and 30 rpm and the results proved statistically significant (p < 0.05). Biogas production at 10, 30, and 67 rpm were 45.6, 48.6, and 52.5 L, respectively. Higher VFA concentrations (7.67 g L−1) were recorded at lower mixing intensity but there was no significant difference in pH and ammonia at different speeds whereas the better mixing efficiency at higher speeds was also the main reason for increase in biogas production. Furthermore, model simulation calculations revealed the reduction of dead zones and better homogeneous mixing at higher mixing speeds. Reduction of dead zones from 18% at 10 rpm to 2% at 67 rpm was observed, which can be the major factor in significant difference in biogas production rates at various mixing intensities. Optimization of digester and impeller geometry should be a prime focus to scale-up digesters and to optimize mixing in full-scale digesters.